Lithium ion secondary battery

By adjusting the composition of the positive electrode sheet and electrolyte of lithium iron phosphate battery, the problem of insufficient performance of the battery under fast charging, high temperature and low temperature conditions is solved, and better cycle performance and low temperature performance are achieved.

CN119447416APending Publication Date: 2025-02-14ZHEJIANG COSMX BATTERY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411362161.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When lithium iron phosphate batteries are fast charging and discharged, lithium ions are slow to transmit and the battery impedance is large, resulting in a temperature rise; under high temperature and extremely low temperature conditions, the battery's cycling and low temperature performance are insufficient.

Method used

By adjusting the mass ratio of Dv50 of lithium iron phosphate particles in the positive electrode sheet, linear organic solvent and cyclic organic solvent in the electrolyte, and the mass ratio of lithium difluorosulfonimide and lithium hexafluorophosphate, it can satisfy the specific relationship and improve the battery low-temperature discharge performance and high-temperature cycle performance.

Benefits of technology

It effectively improves the low-temperature discharge performance and high-temperature circulation performance of the battery, ensuring the stability and performance of the battery under different temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065208400000181
    Figure BDA0005065208400000181
  • Figure BDA0005065208400000191
    Figure BDA0005065208400000191
  • Figure BDA0005065208400000201
    Figure BDA0005065208400000201
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a lithium ion secondary battery. The battery comprises a positive plate, a negative plate and electrolyte, the positive plate comprises lithium iron phosphate particles, and the Dv50 of the lithium iron phosphate particles is 5-15 [mu] m; the electrolyte comprises an organic solvent, and the organic solvent comprises a linear organic solvent and an annular organic solvent; the linear organic solvent comprises linear carbonic ester and linear carboxylic ester, and the cyclic organic solvent comprises cyclic carbonic ester; based on the total mass of the electrolyte, the mass ratio of the cyclic carbonate is recorded as S1, the mass ratio of the linear carbonate is recorded as S2, and the mass ratio of the linear carboxylic ester is recorded as S3; s = (S2 + S3) / S1; s satisfies 1.5 < = S < = 20; the electrolyte comprises lithium bis (fluorosulfonyl) imide and lithium hexafluorophosphate; the mass ratio of the lithium bis (fluorosulfonyl) imide to the lithium hexafluorophosphate is recorded as L, Lgt; 1. The battery provided by the invention has relatively good low-temperature discharge performance and high-temperature cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] Compared with traditional batteries, lithium-ion batteries have advantages such as high specific energy, long cycle life, no pollution, and high operating voltage. Therefore, they have been widely used in many fields such as portable electronic devices, energy storage, and automotive power. In the field of electric vehicles, in addition to power batteries, start-stop batteries are also very important. When the car starts and stops, the battery provides energy, which places great demands on the battery's fast charging performance, power performance, and high-temperature cycle performance.

[0003] Compared with ternary lithium batteries, lithium iron phosphate batteries are cheaper and have a longer service life than lead-acid batteries. More and more car companies are willing to use lithium iron phosphate batteries as start-stop batteries. However, during fast charging and discharging, the lithium iron phosphate positive electrode transmits lithium ions slowly, and the battery impedance is large, resulting in a high temperature rise in the battery; at the same time, the start-stop battery is usually installed near the motor, and its temperature is high, causing the battery to usually charge and discharge at high temperatures, which seriously accelerates the attenuation of the battery capacity. In addition, under extreme conditions, such as -30°C, the start-stop battery also needs to work normally to provide energy for the car to start, so the lithium iron phosphate battery urgently needs to improve its low-temperature performance under extreme low-temperature conditions. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion secondary battery. By adjusting the Dv50 of lithium iron phosphate particles in the positive electrode sheet, the mass ratio of linear organic solvent to cyclic organic solvent in the electrolyte, and the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate, when the three meet a specific relationship, the low-temperature discharge performance of the battery can be effectively improved while taking into account the high-temperature cycle performance.

[0005] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0006] The positive electrode sheet includes lithium iron phosphate particles, and the Dv50 of the lithium iron phosphate particles is denoted as d1 μm; d1 satisfies: 5≤d1≤15;

[0007] The electrolyte includes an organic solvent, and the organic solvent includes a linear organic solvent and a cyclic organic solvent; the linear organic solvent includes a linear carbonate and a linear carboxylate, and the cyclic organic solvent includes a cyclic carbonate; based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate is recorded as S1, the mass proportion of the linear carbonate is recorded as S2, and the mass proportion of the linear carboxylate is recorded as S3; S=(S2+S3) / S1; S satisfies: 1.5≤S≤20;

[0008] The electrolyte includes a lithium salt, and the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is denoted as L, and L>1.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] The lithium-ion secondary battery provided by the present invention can effectively improve the low-temperature discharge performance of the battery while taking into account the high-temperature cycle performance by adjusting the Dv50 of the lithium iron phosphate particles in the positive electrode sheet within a specific range, and containing a linear organic solvent and a cyclic organic solvent in the electrolyte, so that the content of the linear organic solvent is higher than that of the cyclic organic solvent, and the content of lithium bis(fluorosulfonyl)imide is higher than that of lithium hexafluorophosphate.

[0011] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0014] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0015] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0016] The positive electrode sheet includes lithium iron phosphate particles, and the Dv50 of the lithium iron phosphate particles is denoted as d1 μm; d1 satisfies: 5≤d1≤15;

[0017] The electrolyte includes an organic solvent, and the organic solvent includes a linear organic solvent and a cyclic organic solvent; the linear organic solvent includes a linear carbonate and a linear carboxylate, and the cyclic organic solvent includes a cyclic carbonate; based on the total mass of the electrolyte, the mass proportion of the cyclic carbonate is recorded as S1, the mass proportion of the linear carbonate is recorded as S2, and the mass proportion of the linear carboxylate is recorded as S3; S=(S2+S3) / S1; S satisfies: 1.5≤S≤20;

[0018] The electrolyte includes a lithium salt, and the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is denoted as L, and L>1.

[0019] In some embodiments, the Dv50 d1 of the lithium iron phosphate particles satisfies: 5≤d1≤15, and the Dv50 of the lithium iron phosphate particles can be, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or any point value between the ranges formed by the above two point values.

[0020] The electrolyte of traditional lithium iron phosphate batteries has high viscosity at low temperatures and slow lithium ion transmission. At extremely low temperatures (e.g. -30°C), organic solvents in the electrolyte, such as ethylene carbonate (EC) or dimethyl carbonate (DMC), will solidify on the surface of the positive electrode, making it impossible for the positive electrode to be charged and discharged. In addition, traditional start-stop batteries use LiPF6 as the main salt. When the battery is cycled for a long time at high temperatures, LiPF6 is easily decomposed at high temperatures to produce LiF and PF5, causing serious gas production during high-temperature cycling.

[0021] In the electrolyte of the present invention, the content of linear organic solvent is higher than that of cyclic organic solvent (1.5≤S≤20), and good fluidity can be maintained even at extremely low temperatures. The desolvation energy of lithium ions on the positive electrode surface can also be reduced. In combination with lithium iron phosphate with a particle size in a specific range, lithium ions can be quickly transferred from the electrolyte to the interior of the positive electrode lithium iron phosphate particles, thereby reducing the charge transfer impedance and improving the dynamics of the electrolyte. However, when 1.5≤S≤20, the amount of cyclic organic solvent used is relatively low, and the ability of the electrolyte to dissolve lithium salts is relatively low. Since the solubility of lithium bis(fluorosulfonyl)imide in the electrolyte is higher than that of lithium hexafluorophosphate, the present invention adjusts the content of lithium bis(fluorosulfonyl)imide in the electrolyte to be higher than that of lithium hexafluorophosphate (i.e., L>1), the anion radius of LiFSI is larger, the dissociation ability is better, and it is difficult to enter the lithium ion solvation structure. When its content is controlled to be higher than that of lithium hexafluorophosphate, the problem of low solubility of lithium salt caused by low content of cyclic organic solvent can be improved, the content of lithium ions in the electrolyte can be increased, and the electrolyte can have a higher conductivity. Furthermore, PF6 in LiPF6 can be prevented. -A large amount of charge neutralization caused by entering the lithium-ion solvation structure inhibits the decrease in conductivity and reduces the generation of LiF and PF5 to suppress gas production, enabling the electrolyte to have good high-temperature cycling performance and kinetic performance. The Dv50 of the lithium iron phosphate particles is maintained within the range of 5 μm - 15 μm. There are many active sites for effective contact between the positive electrode sheet and the electrolyte, which can promote the functions of linear organic solvents, cyclic organic solvents, lithium bis(fluorosulfonyl)imide, and lithium hexafluorophosphate in the electrolyte, increasing the transport rate of lithium ions at the interface and inside the electrode sheet, reducing the desolvation energy of lithium ions, and improving the discharge performance of the battery at low temperatures.

[0022] In some embodiments, the mass ratio L of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate satisfies: 1 < L ≤ 4. The value of L can be, for example, 1.1, 1.5, 2, 2.5, 3, 3.5, 4, or any value between the above two-point values. Preferably, 1.2 ≤ L ≤ 3. Adjusting the mass ratio L of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate to further satisfy the above range can avoid the situation where when L > 4, the amount of lithium hexafluorophosphate in the electrolyte is too small, and the HF generated by its decomposition is not sufficient to react with the aluminum current collector to form an AlF3 passivation layer to prevent further corrosion. At the same time, it can avoid the situation where when L > 4, the amount of lithium bis(fluorosulfonyl)imide in the electrolyte is too large, and the inevitable LiSO3F impurities therein cause more corrosion products Al(SO3F)3 to be generated during the polarization of the aluminum current collector. Al(SO3F)3 dissolves in the organic solvent to accelerate the corrosion of the aluminum current collector, so the aluminum current collector cannot be passivated, resulting in gas production of the electrolyte on the aluminum current collector and poor high-temperature storage performance of the electrolyte, thereby further improving the conductivity of the electrolyte and the high-temperature cycling performance of the battery.

[0023] In some embodiments, the value of S can be, for example, 1.5, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, or any value within the range composed of the above two-point values. The lower desolvation energy of the linear carboxylic ester can reduce the desolvation energy of lithium ions and further reduce the charge transfer resistance. When S > 20, the mass fraction of the cyclic carbonate is too small, resulting in a decrease in the conductivity of the electrolyte when anions in the electrolyte enter the solvation structure of lithium ions. When S < 1.5, the mass fraction of the cyclic carbonate solvent is too large, increasing the viscosity of the electrolyte at low temperatures and resulting in a decrease in the low-temperature discharge capacity of the battery. When the preferred range 3 ≤ S ≤ 15 is satisfied, the charge and discharge performance and cycling performance under high-temperature and low-temperature conditions can be further improved.

[0024] In some embodiments, the cyclic carbonate includes one or more of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), preferably EC.

[0025] In some embodiments, the mass proportion S1 of the cyclic carbonate satisfies: 2%≤S1≤40%, and the mass proportion S1 of the cyclic carbonate can be, for example, 2%, 4%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 32%, 34%, 36%, 38%, 40% or any point value in the range composed of any two of the above point values, preferably 5%≤S1≤15%; when the mass proportion S1 of the cyclic carbonate is adjusted to further meet the above range, it can promote the dissolution of the lithium salt while avoiding S1 being too large. The high content of cyclic carbonate causes the viscosity of the electrolyte to increase at low temperatures, resulting in the problem that the battery cannot be charged and discharged.

[0026] In some embodiments, the linear carbonate includes one or more of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl propyl carbonate (MPC), preferably EMC.

[0027] In some embodiments, the mass proportion S2 of the linear carbonate satisfies: 10%≤S2≤70%, and the mass proportion S2 of the linear carbonate can be, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any point value in the range composed of the above two point values, preferably 20%≤S2≤50%. When the mass proportion S2 of the linear carbonate is adjusted to further meet the above range, the electrolyte can have better fluidity, further reduce the viscosity of the electrolyte, and improve the charge and discharge efficiency of the battery. Compared with cyclic carbonate solvents, linear carbonate solvents have lower viscosity at low temperatures, so that the battery can be charged and discharged normally at low temperatures, and the low temperature performance of the battery is improved.

[0028] In some embodiments, the linear carboxylic acid ester includes one or more of ethyl propionate (EP), ethyl acetate (EA), propyl propionate (PP), methyl acetate (MA), and methyl propionate (MP), preferably EP.

[0029] In some embodiments, the mass proportion S3 of the linear carboxylic acid ester satisfies: 10%≤S3≤70%, and the mass proportion S3 of the linear carboxylic acid ester can be, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any point value in the range formed by any two of the above point values, preferably 20%≤S3≤50%. When the mass proportion S3 of the linear carboxylic acid ester is adjusted to further meet the above range, the combination of the linear carboxylic acid ester and the linear carbonate can further reduce the viscosity of the electrolyte, improve the kinetics, and greatly improve the charge and discharge efficiency of the battery at low and high temperatures, while avoiding excessive mass proportion of the linear carboxylic acid ester, which aggravates the side reaction of the electrode and causes gas production in the battery.

[0030] By using cyclic carbonate, linear carbonate and linear carboxylic acid ester in combination, the use temperature range of the electrolyte is broadened, and the low-temperature and high-temperature performance of the battery is improved. However, in the electrolyte, the amount of linear carbonate and linear carboxylic acid ester used is greater than that of cyclic carbonate. Under high temperature conditions, the high-temperature gas production of the battery is limited. In order to further inhibit the high-temperature gas production of the battery and improve the dynamic performance of the battery, the present invention further proposes: based on the total mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is recorded as L1, and the mass proportion of lithium hexafluorophosphate is recorded as L2, L=L1 / L2; L1 and L2 satisfy: 8%≤L1+L2≤22%, illustratively, the value of L1+L2 can be, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22% or any point value in the range composed of the above two point values, preferably 10%≤L1+L2≤20%.

[0031] When the total mass of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is adjusted to satisfy the above relationship, it is possible to avoid the situation where the total mass ratio of LiFSI and LiPF6 is too low when L1+L2≤8%, resulting in low conductivity of the electrolyte and poor cycle performance; and avoid the situation where the total mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is too high when L1+L2>22%, resulting in the combination of anions and cations in the electrolyte and a decrease in ionic conductivity; controlling the value of L1+L2 within the above range can further improve the low-temperature discharge performance of the battery.

[0032] In some embodiments, the mass proportion L1 of lithium bis(fluorosulfonyl)imide satisfies: 1%≤L1≤15%, and the mass proportion L1 of lithium bis(fluorosulfonyl)imide can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any point value in the range of the above two point values, preferably 4%≤L1≤10%. When L1 and L2 satisfy 8%≤L1+L2≤22% and L>1, the mass proportion L1 of lithium bis(fluorosulfonyl)imide is adjusted to further meet the above range, the content of lithium bis(fluorosulfonyl)imide in the electrolyte is higher than that of lithium hexafluorophosphate, and lithium bis(fluorosulfonyl)imide has a larger anion radius and better dissociation ability, which can provide better conductivity and electromigration number in the electrolyte; since lithium bis(fluorosulfonyl)imide is more difficult to enter the lithium ion solvation structure, it helps to reduce the adverse reactions of the battery at high temperature, especially the occurrence of high temperature gas production side reaction. Therefore, further adjusting the mass proportion of lithium bis(fluorosulfonyl)imide to meet the above range can enable the battery to be used at higher temperatures, improve kinetics, inhibit high-temperature gas production side reactions, and take into account the high-temperature performance of the battery.

[0033] In some embodiments, the mass proportion L2 of lithium hexafluorophosphate satisfies: 1%≤L1≤15%, and the mass proportion L2 of lithium hexafluorophosphate can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any point value in the range of the above two point values, preferably 5%≤L1≤12%. When L1 and L2 satisfy 8%≤L1+L2≤22%, and the mass proportion L2 of lithium hexafluorophosphate is adjusted to meet the above range, the decomposition reaction of lithium hexafluorophosphate at high temperature can be further avoided to generate LiF and PF5, and the gas production of the battery during high-temperature cycling can be inhibited; the lithium ion migration rate of the battery is increased, the charge and discharge performance of the battery at high rates is improved, and the high-temperature cycling performance of the battery is further improved.

[0034] In some embodiments, L, S, and d1 satisfy: For example, The value of can be, for example, 0.2, 0.3, 0.4, 0.5, 1, 1.5, 2, 2.5, 2.6, 2.7, 2.8, 2.9, 3 or any point value within the range formed by any two of the above points. When L, S and d1 satisfy When the battery is heated, the conductivity of the electrolyte can be further improved, the impedance can be reduced, the low-temperature discharge performance of the battery can be improved, and the increase of high-temperature gas production of the battery can be further suppressed; it can also avoid When the battery is heated, the gas production increases, avoiding When the electrolyte is too weak, the transport of lithium ions is affected.

[0035] In some embodiments, the lithium iron phosphate particles include secondary particles composed of primary particles. The Dv50 of the secondary particles is the DV50 of the lithium iron phosphate, that is, d1 is 5μm-15μm, and the Dv50 of the secondary particles can be, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any point value in the range of the above two point values; the Dv50 of the primary particles is 0.5μm-2.5μm, and the Dv50 of the primary particles can be, for example, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, or any point value in the range of the above two point values. The Dv50 of the primary particles further meets the above range, which can further shorten the transmission distance of lithium ions inside the positive electrode active material particles, enhance the rapid transmission of lithium ions inside the particles, and thereby improve the discharge performance of the battery at low temperatures.

[0036] It should be noted that the "primary particle" in the present invention refers to a single lithium iron phosphate particle; the "secondary particle" refers to a particle formed by the agglomeration of several primary particles, for example: the secondary particle is a particle formed by the agglomeration of 2 primary particles, a particle formed by the agglomeration of 5 primary particles, a particle formed by the agglomeration of 10 primary particles, a particle formed by the agglomeration of 50 primary particles, or a particle formed by the agglomeration of 100 primary particles.

[0037] In the present invention, the term "Dv50" refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of the lithium iron phosphate particle sample reaches 50%. Dv50 can be tested using a laser particle size analyzer.

[0038] In some embodiments, the lithium iron phosphate particles are doped with Ti element and / or V element. For example, Ti element, V element, or both Ti element and V element can be doped in the lithium iron phosphate particles, preferably Ti element and V element are doped at the same time. In the lithium iron phosphate particles, the content of Ti element and / or V element is ≤1%, for example, it can be 0.01%, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1% or any point value in the range of the above two point values, preferably the total content of Ti element and V element is ≤1%. Further doping Ti element and V element in the lithium iron phosphate particles can form a fast ion conductor at the interface, and by forming Li-Ti-O or Li-VO electrostatic interaction, the solvation energy of lithium ions is reduced, and the transmission speed of lithium ions between the electrolyte and the positive electrode particles can be further improved, thereby improving the power performance of the positive electrode.

[0039] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, and the positive electrode active material layer includes lithium iron phosphate particles.

[0040] In some embodiments, the single-surface density w1 of the positive electrode sheet is 8 mg / cm 2 -12 mg / cm 2 , w1 can be 8 mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 、10mg / cm 2 、10.5mg / cm 2 、11mg / cm 2 、11.5mg / cm 2 , 12mg / cm 2Or any point value in the range composed of any two of the above point values; and / or, the single-sided thickness h1 of the positive electrode active material layer is 50μm-70μm, and h1 can be, for example, 50μm, 52μm, 54μm, 56μm, 58μm, 60μm, 62μm, 64μm, 66μm, 68μm, 70μm or any point value in the range composed of any two of the above point values. When the single-sided surface density w1 of the positive electrode sheet and / or the single-sided thickness h1 of the positive electrode active material layer are adjusted to further meet the above range, it is possible to avoid the situation where w1 is too large, the transmission distance of ions in the positive electrode material increases, the internal resistance of the battery increases, the polarization increases, the low-temperature start-up of the battery is affected, and the cycle performance deteriorates; when h1 is too small, the effective contact area between the positive electrode active material layer and the electrolyte is reduced, the wettability of the electrolyte is reduced, and at the same time, under low temperature conditions, the positive electrode active material layer is too thin to provide sufficient reaction active area, so that the reaction rate between the positive electrode active material and the electrolyte decreases. The reduction in reaction rate at low temperature limits the charge and discharge performance of the battery, resulting in a decrease in low temperature performance; when w1 and h1 further meet the above range, the energy transmission rate of lithium ions between the positive electrode particles can be further accelerated, thereby improving the cycle performance and low-temperature charge and discharge performance of the battery.

[0041] In some embodiments, the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode collector, the negative electrode active material layer includes a negative electrode active material; the Dv50 of the negative electrode active material is recorded as d2μm, d2 satisfies: 4≤d2≤10, d2 can be, for example, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm or any point value in the range composed of any two of the above point values. Adjusting the Dv50 of the negative electrode active material to further meet the above range can shorten the internal transmission distance of lithium ions in the active material particles, further increase the transmission speed of lithium ions in the active material, and improve the charge and discharge performance of the battery; avoid Dv50 being too large, which will cause increased polarization, faster battery cycle decay, and too low capacity retention rate; at the same time, avoid Dv50 being too small, with too many active sites, which will increase battery gas production and accelerate capacity decay.

[0042] In some embodiments, the single surface density w2 of the negative electrode sheet is 3 mg / cm 2 -7 mg / cm 2 , w2 can be 3 mg / cm 2 、3.5mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 , 6mg / cm2 、6.5mg / cm 2 , 7mg / cm 2 Or any point value in the range of the above two point values; and / or, the single-sided thickness h2 of the negative electrode active material layer is 25μm-45μm, and h2 can be, for example, 25μm, 27μm, 29μm, 31μm, 33μm, 35μm, 37μm, 39μm, 41μm, 43μm, 45μm or any point value in the range of the above two point values. Adjusting the single-sided surface density w2 of the negative electrode sheet and / or the single-sided thickness h2 of the negative electrode active material layer to further meet the above range can further accelerate the transmission rate of lithium ions between the negative electrode particles and improve the cycle performance and low-temperature charge and discharge performance of the battery.

[0043] In some embodiments, the negative electrode active material includes a composite material of one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-carbon, silicon-oxygen, nano-silicon, and silicon alloy.

[0044] In some embodiments, the negative electrode active material includes artificial graphite and / or natural graphite, and the graphitization degree G of the artificial graphite and / or natural graphite satisfies: 88%≤G≤95%, and G can be, for example, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or any point value in the range of the above two point values. When the negative electrode active material is selected from graphite, and the graphitization degree G is adjusted to further meet the above range, the charging capacity of the negative electrode can be further improved, and a stable SEI film can be generated on the surface of the pole piece; to avoid the negative electrode graphitization being too low, the surface defects of the graphite are more, the electrolyte decomposes more on the surface, and the gas production increases.

[0045] Exemplarily, the graphitization degree G can be measured by the following method: using XRD diffraction method to measure the graphite crystal plane structure interlayer spacing d002; the graphitization degree G is calculated using Franklin's formula: G = (0.3440-d002) / (0.3440-0.3354)×100%.

[0046] In the present invention, by setting the positive and negative electrode membranes as mentioned above, it is possible to ensure that lithium ions are quickly transferred inside the active material particles, between the particles, and between the positive and negative electrodes, so that the battery has better ultimate power and fast charging performance, and has better charging and discharging capabilities at high rates, high temperatures or low temperatures. However, the start-stop battery is usually installed at the negative electrode, which makes the ambient temperature of the start-stop battery relatively high. At high temperatures, the side reactions of the electrolyte with the positive and negative electrodes increase, the interface damage is accelerated, the active lithium is severely consumed, the capacity decay of the battery is accelerated, and the battery is prone to gassing and expansion at high temperatures. In order to further improve the long cycle performance of the battery at high temperatures, the present invention further proposes: the electrolyte includes a first additive; the mass proportion of the first additive is recorded as a1 based on the total mass of the electrolyte;

[0047] The electrolyte includes a second additive, the second additive includes a sulfur-containing additive and / or a boron-containing additive; illustratively, the second additive may be a sulfur-containing additive alone, a boron-containing additive alone, or a combination of a sulfur-containing additive and a boron-containing additive, preferably a combination of a sulfur-containing additive and a boron-containing additive; based on the total mass of the electrolyte, the mass proportion of the second additive is denoted as a2;

[0048] The electrolyte includes a third additive, and the third additive includes a phosphorus-containing additive; the mass proportion of the third additive is denoted as a3 based on the total mass of the electrolyte;

[0049] a1, a2 and a3 satisfy: For example, The value of can be, for example, 1, 3, 5, 7, 9, 11, 13, 15, 17, 19, 21, 23, 25 or any point value in the range of any two of the above points. Further adding a first additive, a second additive and a third additive to the electrolyte and adjusting the content of the additives When the above range is met, the active sites exposed by the positive and negative electrodes due to the dissolution of active substances, decomposition and gas production of electrolytes, and cracking of electrode materials during the cycle can be effectively repaired, thereby forming a stable interface, reducing the consumption of electrode materials and electrolytes, reducing polarization during battery charging and discharging, and further improving the high-temperature cycle performance of the battery, avoiding When the first additive and the second additive have a relatively low mass ratio, they are easily consumed completely in the battery formation stage, and are not sufficient to repair the newly exposed interface during the high-temperature cycle process, resulting in an insufficiently tight interface, causing direct contact between the electrolyte and the active sites of the positive and negative electrodes, resulting in a large amount of decomposition and consumption of the electrolyte, and increased gas production.

[0050] In some embodiments, the first additive is a carbonate additive, mainly used as a negative electrode film-forming additive, and the carbonate additive includes one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC), among which a combination of VC and FEC is preferred.

[0051] In some embodiments, the mass proportion a1 of the first additive satisfies: 0.1%≤a1≤6%, and the mass proportion a1 of the first additive can be, for example, 0.1%, 0.2%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any point value in the range of the above two point values, preferably 0.5%≤a1≤4%. When the mass proportion a1 of the first additive further satisfies the above range, it can avoid that when a1<0.1%, the negative electrode interface formed during battery formation is not stable enough, resulting in a decrease in battery performance and increased gas production during high-temperature storage; when a1>6%, the first additive content is too high, causing the electrolyte viscosity to increase, the impedance to increase, and the battery's low-temperature cold start is poor; the first additive reacts at the new active sites exposed on the surface of the negative electrode particles to generate an interface, further preventing the electrolyte from reacting at the active sites to produce gas.

[0052] In some embodiments, the second additive includes a sulfur-containing additive and / or a boron-containing additive, mainly used as a high-temperature additive, wherein the sulfur-containing additive includes one or more of vinyl sulfate (DTD), 1,3-propane sultone (PS), methylene disulfonate (MMDS), vinyl sulfite (ES), and thiophene, wherein a combination of ES and thiophene is preferred; the boron-containing additive includes one or more of tris(trimethylsilyl)borate (TMSB), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), and lithium tetrafluoroborate (LiBF4). The second additive is mainly used as a high-temperature additive.

[0053] In some embodiments, the mass proportion a2 of the second additive satisfies: 0.1%≤a2≤4%, and the mass proportion a2 of the second additive can be, for example, 0.1%, 0.2%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or any point value in the range of the above two point values, preferably 0.2%≤a2≤3%. When the mass proportion a2 of the second additive further satisfies the above range, it can avoid the rapid capacity decay of the battery during the fast charge cycle when a2<0.1; avoid the increase of electrolyte impedance and deterioration of the battery's limit power when a2>4; the second additive will repair the new active sites exposed by the positive electrode during the high temperature and long cycle process, thereby inhibiting the decomposition and gas production of other substances in the electrolyte.

[0054] In some embodiments, the third additive includes a phosphorus-containing additive, mainly as a low-impedance additive, and the phosphorus-containing additive includes one or more of tris(trimethylsilyl)phosphate (TMSP), tris(trimethylsilyl)phosphite (TMSPi), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate)phosphate (LiODFP), and lithium tetrafluorooxalate phosphate (LiOTFP), among which LiPO2F2 is preferred.

[0055] In some embodiments, the mass proportion a3 of the third additive satisfies: 0.1%≤a3≤2%, and the mass proportion a3 of the third additive can be, for example, 0.1%, 0.2%, 0.3%, 0.5%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2% or any point value in the range of the above two point values, preferably 0.2%≤a3≤1.5%. When the mass proportion a3 of the third additive further satisfies the above range, the third additive generates an interface rich in P elements on the surface of the active material, and the interface has a lower interface impedance, which can accelerate the transmission rate of lithium ions, reduce the impedance increase caused by the addition of the first additive and the second additive, and further reduce the film formation impedance of the battery; when a3>2%, a large amount of the third additive will remain in the electrolyte, causing decomposition and gas production; when a3<0.1%, the third additive is completely decomposed during formation, and an interface rich in P elements cannot be formed in the later stage of the battery cycle, and the effect of reducing the film formation impedance is poor.

[0056] In the present invention, the type of the diaphragm base film is not specifically limited, and conventional diaphragm base film types in the art may be selected, for example, including but not limited to polyethylene (PE), polypropylene (PP) or a composite structure of polyethylene and polypropylene.

[0057] In the present invention, the rubber coating layer on the surface of the diaphragm includes one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylic resin, polymethyl acrylate, butyl acrylate-acrylonitrile copolymer, polyacrylonitrile, ethylene-acrylic acid copolymer, polyethyl acrylate, and sodium carboxymethyl cellulose.

[0058] In some embodiments, the diaphragm further includes a ceramic layer; the ceramic layer includes one or more of aluminum oxide, aluminum hydroxide, magnesium oxide, aluminum oxide, zirconium oxide, titanium oxide, and silicon oxide.

[0059] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0061] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0062] Example 1-1

[0063] (1) Preparation of positive electrode

[0064] Lithium iron phosphate powder, polyvinylidene fluoride, acetylene black, and carbon nanotubes were put into a vacuum mixer according to a mass ratio of 96:2:1.5:0.5, and N-methylpyrrolidone (NMP) was added. The mixture was fully mixed under the action of the vacuum mixer until a uniform and fluid positive electrode slurry was formed, wherein the solid content was 55wt%; the positive electrode slurry was evenly coated on a carbon-coated aluminum foil with a thickness of 12μm, and the coating single-side surface density was 10mg / cm 2 After drying and roller pressing, the thickness of the active material is controlled to be 60 μm, and then the positive electrode sheet is obtained by striping and punching.

[0065] (2) Preparation of negative electrode sheet

[0066] Graphite (graphitization degree of 93%), styrene-butadiene rubber, sodium carboxymethyl cellulose and acetylene black were put into a vacuum mixer in a mass ratio of 96.5:1:1:1.5, and deionized water was added. The mixture was fully mixed under the action of the vacuum mixer to finally form a uniform and fluid negative electrode slurry with a solid content of 45wt%. The negative electrode slurry was evenly coated on a copper foil with a thickness of 6μm, and the coating single-side surface density was 5mg / cm 2 , drying, roller pressing, controlling the thickness of the active material to 35 μm, and die cutting to obtain the negative electrode sheet.

[0067] (3) Preparation of electrolyte

[0068] In an argon glove box with a water content of <0.1ppm and an oxygen content of <0.1ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl propionate (EP) are mixed evenly in a mass ratio of 2:9:9, and fully dried lithium hexafluorophosphate (LiPF6) and bis(fluorosulfonyl)imide lithium salt LiFSI are added thereto for stirring and dissolution. Based on the total mass of the electrolyte, the mass proportions of LiPF6 and LiFSI are 6.5% and 10%, respectively. 2.5% of vinylene carbonate (VC) based on the total mass of the electrolyte is added, 0.5% of vinyl sulfite (ES) based on the total mass of the electrolyte, 0.5% of thiophene, and 0.5% of vinyl sulfate (DTD) are added, and 1.0% of lithium difluorophosphate LiPO2F2 based on the total mass of the electrolyte is added, stirred evenly, and the electrolyte is obtained after passing the physical property test.

[0069] (4) Preparation of batteries

[0070] The positive electrode sheet obtained in step (2), the negative electrode sheet obtained in step (3) and the isolation film (PP) are wound to obtain a bare battery cell; the bare battery cell is welded with a pole ear and placed in a battery casing, and the electrolyte prepared in step (3) is injected into the dried and qualified battery cell, and a battery is obtained after standing, aging, formation, exhaust, aging, sorting and other processes.

[0071] (5) Test battery

[0072] Using the Blue Electric charge and discharge test cabinet, the electrochemical performance of the battery is tested using the following test methods:

[0073] (i) Fast charging cycle performance test

[0074] High temperature fast charge cycle performance test: At 45°C, use a vernier caliper to measure the thickness Q1 of the battery before cycling, charge the divided battery to 3.65V at 3C constant current and constant voltage, with a cut-off current of 0.05C, and then discharge it to 2.5V at 3C constant current, record the initial discharge capacity, and repeat this cycle. After 3000 cycles of charge and discharge, calculate the capacity retention rate at the 3000th week, and record the battery thermal thickness Q2 at the same time. The calculation formula is as follows:

[0075] 3000th cycle capacity retention rate (%) = (3000th cycle discharge capacity / first cycle discharge capacity) × 100%.

[0076] The battery expansion rate at the 3000th cycle (%) = (battery thickness Q2 at the 3000th cycle / battery thickness Q1 before the cycle) × 100%.

[0077] (ii) Low temperature cold start test

[0078] At 25°C, charge the divided battery to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and then discharge it to 2.5V at 1C constant current, and record the initial discharge capacity C0. Discharge the battery to 50% SOC at 1C, leave it at -30°C for 4 hours, and then discharge it to the lower limit voltage of 2.5V at 10C rate, and record the discharge time. The longer the discharge time, the better the cold start performance.

[0079] Example 1-3, and Comparative Examples 1-8 are carried out with reference to Example 1-1, and the main differences are shown in Table 1. Among them, the Dv50 of lithium iron phosphate is changed in Example 1. The mass proportion of linear organic solvent and cyclic organic solvent in the electrolyte is changed in Example 2. The ratio of LIFSI and LIPF6 in the electrolyte is changed in Example 3. The Dv50 of lithium iron phosphate in Comparative Example 1 is too small and is not within the protection range. The Dv50 of lithium iron phosphate in Comparative Example 2 is not within the protection range. The ratio S of linear organic solvent to cyclic organic solvent in Comparative Example 3 is not within the protection range. No cyclic organic solvent is added to Comparative Example 4. In Comparative Example 5, the ratio L of LIFSI and LIPF6 is less than 1. In Comparative Example 6, no linear carboxylate is added to the electrolyte. In Comparative Example 7, the proportion of linear organic solvent in the electrolyte is less than the proportion of cyclic organic solvent. In Comparative Example 8, no LIFSI is added to the electrolyte.

[0080] Table 1

[0081]

[0082] Note: “ / ” indicates that the corresponding substance was not added or the corresponding parameter was not tested.

[0083] As can be seen from Table 1, the present invention adjusts the Dv50 (d1) of the lithium iron phosphate particles to satisfy 5 ≤ d1 ≤ 15, adjusts the mass ratio of cyclic carbonate (S1), the mass ratio of linear carbonate (S2), and the mass ratio of linear carboxylic acid ester (S3), so that the ratio of linear organic solvent to cyclic organic solvent (S = (S2 + S3) / S1) satisfies 1.5 ≤ S ≤ 20, and adjusts the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate (L) > 1, thereby effectively improving the low temperature discharge performance and high temperature cycle performance of the battery.

[0084] The examples 4 to 6 were carried out with reference to the examples 1-1, and the main differences are shown in Table 2. Among them, the example 4 group changed the mass proportion of the first additive in the electrolyte (a1). The example 5 group changed the mass proportion of the second additive in the electrolyte (a2). The examples 6-1 and 6-2 changed the mass proportion of the third additive in the electrolyte (a3). In the example 6-3, a1, a2, and a3 were all changed.

[0085] Table 2

[0086]

[0087] It can be seen from Table 2 that the present invention can further improve the high temperature cycle performance of the battery while taking into account the low temperature discharge performance of the battery by adjusting the mass ratio of the first additive (a1), the second additive (a2) and the third additive (a3) ​​in the electrolyte to satisfy 1≤(a1+a2) / a3≤25.

[0088] The Example 7 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 3. Among them, in the Example 7 group, the mass proportion of lithium salt (LIFSI and LIPF6) in the electrolyte was changed.

[0089] Table 3

[0090]

[0091] It can be seen from Table 3 that the present invention can further improve the low-temperature discharge performance and high-temperature cycle performance of the battery by adjusting the mass ratio of LIFSI and LIPF6.

[0092] The examples 8-11 were carried out in accordance with the examples 1-1, and the main differences are shown in Table 4. Among them, the example 8 changed the single-sided surface density of the positive electrode sheet (w1). The example 9 changed the single-sided thickness of the positive electrode active material layer (h1). The example 10 changed the single-sided surface density of the negative electrode sheet (w2). The example 11 changed the single-sided thickness of the negative electrode active material layer (h2).

[0093] Table 4

[0094]

[0095]

[0096] Note: “*” indicates that the corresponding parameters in this embodiment or comparative example are the same as those in Example 1-1.

[0097] It can be seen from Table 4 that the present invention can improve the wettability of the electrode sheet by the electrolyte by adjusting the single-sided surface density of the positive and negative electrode sheets and the single-sided thickness of the positive and negative electrode active material layers, thereby further improving the low-temperature discharge performance and high-temperature cycle performance of the battery.

[0098] The Example 12 group was carried out in accordance with the Example 1-1, and the main differences are shown in Table 5. In the Example 12 group, the Dv50 (d2) of the negative electrode active material was changed.

[0099] Table 5

[0100]

[0101] It can be seen from Table 5 that the present invention can shorten the transmission distance of lithium ions inside the active material particles by adjusting the Dv50 (d2) of the negative electrode active material, thereby further improving the charge and discharge performance of the battery.

[0102] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte solution; The positive electrode sheet includes lithium iron phosphate particles, and the Dv50 of the lithium iron phosphate particles is denoted as d1 μm; d1 satisfies: 5 ≤ d1 ≤ 15; The electrolyte solution includes an organic solvent, and the organic solvent includes a linear organic solvent and a cyclic organic solvent; the linear organic solvent includes a linear carbonate and a linear carboxylate, and the cyclic organic solvent includes a cyclic carbonate; based on the total mass of the electrolyte solution, the mass ratio of the cyclic carbonate is denoted as S1, the mass ratio of the linear carbonate is denoted as S2, and the mass ratio of the linear carboxylate is denoted as S3; S = (S2 + S3) / S1; S satisfies: 1.5 ≤ S ≤ 20; The electrolyte solution includes a lithium salt, and the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is denoted as L, and L > 1.

2. The lithium ion secondary battery according to claim 1, characterized in that: S satisfies: 3 ≤ S ≤ 15; Preferably, S1 satisfies: 2% ≤ S1 ≤ 40%, more preferably 5% ≤ S1 ≤ 15%; Preferably, S2 satisfies: 10% ≤ S2 ≤ 70%, more preferably 20% ≤ S2 ≤ 50%; Preferably, S3 satisfies: 10% ≤ S3 ≤ 70%, more preferably 20% ≤ S3 ≤ 50%.

3. The lithium ion secondary battery according to claim 1, characterized in that: Based on the total mass of the electrolyte solution, the mass ratio of lithium bis(fluorosulfonyl)imide is denoted as L1, and the mass ratio of lithium hexafluorophosphate is denoted as L2, and L = L1 / L2; L satisfies: 1 < L ≤ 4, preferably 1.2 ≤ L ≤ 3; L1 and L2 satisfy: 8% ≤ L1 + L2 ≤ 22%, preferably 10% ≤ L1 + L2 ≤ 20%; Preferably, L1 satisfies: 1% ≤ L1 ≤ 15%, more preferably 4% ≤ L1 ≤ 10%; Preferably, L2 satisfies: 1% ≤ L1 ≤ 15%, more preferably 5% ≤ L1 ≤ 12%.

4. The lithium-ion secondary battery according to claim 1, characterized in that: The lithium iron phosphate particles include secondary particles composed of primary particles; Preferably, the Dv50 of the secondary particles is 5 μm - 15 μm; Preferably, the Dv50 of the primary particles is 0.5 μm - 2.5 μm; Preferably, the lithium iron phosphate particles are doped with Ti element and / or V element; Preferably, in the lithium iron phosphate particles, the content of Ti element and / or V element ≤ 1%; 5. The lithium ion secondary battery according to claim 1, characterized in that: L, S and d1 satisfy: Best 6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The electrolyte solution includes a first additive; based on the total mass of the electrolyte solution, the mass ratio of the first additive is denoted as a1; the first additive includes one or more of vinylene carbonate, vinyl ethylene carbonate, and fluoroethylene carbonate; The electrolyte solution includes a second additive, and the second additive includes a sulfur-containing additive and / or a boron-containing additive; based on the total mass of the electrolyte solution, the mass ratio of the second additive is denoted as a2; The electrolyte solution includes a third additive, and the third additive includes a phosphorus-containing additive; based on the total mass of the electrolyte solution, the mass ratio of the third additive is denoted as a3; a1, a2 and a3 satisfy: Best Preferably, a1 satisfies: 0.1% ≤ a1 ≤ 6%, more preferably 0.5% ≤ a1 ≤ 4%; Preferably, a2 satisfies: 0.1% ≤ a2 ≤ 4%, more preferably 0.2% ≤ a2 ≤ 3%; Preferably, a3 satisfies: 0.1% ≤ a3 ≤ 2%, more preferably 0.2% ≤ a3 ≤ 1.5%.

7. The lithium ion secondary battery according to claim 6, characterized in that: The sulfur-containing additive includes one or more of vinyl sulfate, 1,3-propane sultone, methylene methane disulfonate, vinyl sulfite, and thiophene; And / or, the boron-containing additive includes one or more of tris(trimethylsilyl)borate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium tetrafluoroborate; And / or, the phosphorus-containing additive includes one or more of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, lithium difluorophosphate, lithium difluorobisoxalatephosphate, and lithium tetrafluorooxalatephosphate.

8. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, wherein the positive electrode active material layer comprises lithium iron phosphate particles; And / or, the single surface density w1 of the positive electrode sheet is 8 mg / cm 2 -12 mg / cm 2 ; And / or, the single-side thickness h1 of the positive electrode active material layer is 50 μm-70 μm.

9. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material; the Dv50 of the negative electrode active material is denoted as d2 μm, and d2 satisfies: 4≤d2≤10; And / or, the single surface density w2 of the negative electrode sheet is 3 mg / cm 2 -7 mg / cm 2 ; And / or, the single-side thickness h2 of the negative electrode active material layer is 25 μm-45 μm; And / or, the negative electrode active material comprises a composite material of one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-carbon, silicon-oxygen, nano-silicon, and silicon alloy; Preferably, the negative electrode active material comprises artificial graphite and / or natural graphite, and the graphitization degree G of the artificial graphite and / or natural graphite satisfies: 88%≤G≤95%.

10. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that: The cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate, and butylene carbonate, preferably ethylene carbonate; and / or, the linear carbonate comprises one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, preferably ethyl methyl carbonate; And / or, the linear carboxylic acid ester includes one or more of ethyl propionate, ethyl acetate, propyl propionate, methyl acetate, methyl propionate, preferably ethyl propionate.

Citation Information

Cited By

  • Lithium ion battery electrolyte and lithium ion battery

    CN120127225A

  • Battery cell, battery device and electric device

    CN121215859A

  • Electrolyte additive, electrolyte and lithium battery

    CN122716433A

  • Battery

    WO2026201167A1